Blood leptin levels in patients with osteoarthritis: relation to clinical conditions of diseases - Novoseletskyi, Valerii; Stanislavchuk, Mykola (ScienceRise: Medical Science, 2018)
Aim of the work: study of the content of leptin in the serum of patients with OA and the study of relationships with clinical manifestations and functional status of patients. Objects and methods: The determination of blood serum leptin levels and for the evaluation of the Lequesne index, HAQ, and KOOS was performed on 71 female with knee joints OA and 32 healthy women in control group. Results. There was a significant relationship between serum leptin levels and the HAQ scale (p=0.026) and significant differences in the level of leptin in the X-ray stage of OA (p=0.043). An association of excess body weight with an increase in the level of serum leptin in the level of the tendency is established. Conlusions: A detailed analysis of the level of leptin in relation to clinical and demographic indicators, clinical manifestations and functional status of patients with OA revealed a significant difference in the level of leptin in the context of the X-ray stage of OA. A reliable link between the level of leptin and the functional status of patients with HAQ was found. In addition, the association of excess body weight with the increase in the level of serum leptin in the bloodstream was observed at the level of the trend.